2009
DOI: 10.1200/jco.2008.18.2717
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Sorafenib in Metastatic Thyroid Cancer

Abstract: Sorafenib is reasonably well-tolerated therapy with clinical and biologic antitumor activity in metastatic PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
329
5
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(361 citation statements)
references
References 31 publications
15
329
5
12
Order By: Relevance
“…New smallmolecule protein-kinase inhibitors including axitinib [259], sorafenib [260,284,285], motesanib [262] and pazopanib [264] have shown promise in clinical trials on thyroid cancer. PLX4032 (also known as vemurafenib), a BRAF-V600E-specific inhibitor, has been recently approved by the FDA for the treatment of BRAFV600E-positive melanoma [286].…”
Section: Discussionmentioning
confidence: 99%
“…New smallmolecule protein-kinase inhibitors including axitinib [259], sorafenib [260,284,285], motesanib [262] and pazopanib [264] have shown promise in clinical trials on thyroid cancer. PLX4032 (also known as vemurafenib), a BRAF-V600E-specific inhibitor, has been recently approved by the FDA for the treatment of BRAFV600E-positive melanoma [286].…”
Section: Discussionmentioning
confidence: 99%
“…Our study results might also be pertinent to therapeutic decision-making. There is growing evidence that BRAF mutation-targeted therapy (sorafenib) is effective in metastatic or advanced thyroid cancer [26][27][28]. There was also a report that in iodine-refractory differentiated thyroid cancer, an early 18 F-FDG PET response was useful for identifying sorafenib non-responders, although no BRAF mutation analysis was performed in those patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…These findings have suggested that sorafenib may significantly improve outcomes in patients with DTC. Several Phase II trials have assessed the effects of sorafenib monotherapy in over 200 patients with thyroid cancer, most with DTC, with other patients having medullary and anaplastic carcinomas (14)(15)(16)(17)(18)(19)(20). The median progression-free survival (PFS) ranged from 14 to 24 months, with PR rates as high as 38%, and disease control rates (defined as SD plus PR) of 59%-100%.…”
Section: Adverse Eventsmentioning
confidence: 99%